2017
DOI: 10.1038/ncomms15280
|View full text |Cite
|
Sign up to set email alerts
|

The essential role of YAP O-GlcNAcylation in high-glucose-stimulated liver tumorigenesis

Abstract: O-GlcNAcylation has been implicated in the tumorigenesis of various tissue origins, but its function in liver tumorigenesis is not clear. Here, we demonstrate that O-GlcNAcylation can enhance the expression, stability and function of Yes-associated protein (YAP), the downstream transcriptional regulator of the Hippo pathway and a potent oncogenic factor in liver cancer. O-GlcNAcylation induces transformative phenotypes of liver cancer cells in a YAP-dependent manner. An O-GlcNAc site of YAP was identified at T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
229
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(239 citation statements)
references
References 66 publications
9
229
1
Order By: Relevance
“…Recently, a link between glucose concentration and Hippo pathway activity has emerged, wherein glucose deprivation or bioenergetic stress activates AMPK and LATS1/2, which phosphorylate and inactivate Yap (DeRan et al , ; Enzo et al , ; Gailite et al , ; Mo et al , ; Wang et al , ). The importance of lipid and glucose levels in the regulation of the Hippo pathway is best exemplified by elegant work demonstrating the activation of TEAD and Yap directly by palmitoylation (Chan et al , ) and O‐GlcNAcylation (Zhang et al , ), respectively. Together, these studies indicate that Yap activity is tightly regulated by the energetic state of the cell, particularly lipid and glucose supply.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a link between glucose concentration and Hippo pathway activity has emerged, wherein glucose deprivation or bioenergetic stress activates AMPK and LATS1/2, which phosphorylate and inactivate Yap (DeRan et al , ; Enzo et al , ; Gailite et al , ; Mo et al , ; Wang et al , ). The importance of lipid and glucose levels in the regulation of the Hippo pathway is best exemplified by elegant work demonstrating the activation of TEAD and Yap directly by palmitoylation (Chan et al , ) and O‐GlcNAcylation (Zhang et al , ), respectively. Together, these studies indicate that Yap activity is tightly regulated by the energetic state of the cell, particularly lipid and glucose supply.…”
Section: Discussionmentioning
confidence: 99%
“…(Figure A). Since O‐GlcNAcylation is reported to be an important factor affecting protein stability, we therefore investigated whether stimulation of O‐GlcNAcylation inhibits DDX5 degradation. To clarify whether down‐regulation of O‐GlcNAcylation alters the stability of DDX5, SW480 cells with or without OGT knockdown were treated with cycloheximide to inhibit protein synthesis, and then the remaining DDX5 was detected.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies have also found that higher levels of O‐GlcNAcylation are involved in the malignant clinicopathological features of various cancer patients . In gastric carcinoma, poorly differentiated tumours (grades II and III) showed significantly higher expression of O‐GlcNAcylation than grade I tumours .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations